Addressing academic challenges: A quasi-experimental study on the effect of remedial exam strategy for nursing students with low academic performance - Eman M. Gaber Hassan (Belitung Raya Foundation, Indonesia, 2023)
Background: Universities are responsible for providing education and support to all students, including those who may be underachieving. To fulfill this responsibility, universities need effective strategies to help these students graduate successfully. Objective: This study aimed to evaluate the effectiveness of a midterm remedial exam strategy in improving the academic performance of nursing students. Methods: A quasi-experimental design was employed to conduct this research at a private college in Dammam, Saudi Arabia’s eastern region. The study included 306 convenient bachelor nursing students who had failed their midterm exam. Of these, 103 students voluntarily participated in the remedial midterm exam (intervention group) to enhance their midterm scores, while 203 students did not take the remedial exam (control group). Data collection took place in the spring of 2022 by reviewing course files and student records, encompassing formative and summative evaluations across 14 courses. Data analysis involved using SPSS (2023) and Jamovi (version 2.3, 2022) software to conduct paired t-tests, Mann-Whitney, and correlational tests. Results: The remedial group demonstrated significant differences between their midterm and remedial exam scores. However, only 15.5% of students in the remedial group passed the exam, despite 68% showing improvement. Additionally, there were significant differences between the intervention and control groups in midterm and overall course scores. The control group outperformed the remedial group in the midterm, final exams, and overall course scores (p <0.05). Conclusion: Remedial exams can be beneficial for students who are close to passing but may not effectively support those who perform poorly. To address this, implementing a comprehensive remedial program or providing ongoing remedial activities throughout the course can offer better support for strongly underperforming students. Additionally, educational institutions can enhance students’ motivation and performance by providing study skills classes and time-management workshops, equipping them with valuable tools for academic success.